1984
DOI: 10.1093/bja/56.11.1219
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Intracranial Hypertension During Laryngoscopy and Endotracheal Intubation

Abstract: In nine patients, with preoperative ICP monitoring, anaesthesia was induced with thiopentone 5 mg kg-1 given over 1 min, followed by pancuronium 0.1 mg kg-1. After manual hyperventilation with nitrous oxide and oxygen for 3 min they were given thiopentone 2.5 mg kg-1 over 30 s (phase 1); 30 s later laryngoscopy was performed and topical analgesia administered to the larynx. Endotracheal intubation was performed 1 min after spraying the cords (phase 2). The measurements continued for a further 5 min during whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The mean arterial pressure in the second dose thiopentone group increased, following laryngoscopy and intubation, by only 18.7 mmHg from the preinduction value, compared with 23.7 mmHg increase in the control group. This is compatible with the findings of Unni (18) and Cowarker who used the second dose thiopentone at a dose of 2.5 mg/kg over 30 seconds before laryngoscopy.…”
Section: Discussionsupporting
confidence: 91%
“…The mean arterial pressure in the second dose thiopentone group increased, following laryngoscopy and intubation, by only 18.7 mmHg from the preinduction value, compared with 23.7 mmHg increase in the control group. This is compatible with the findings of Unni (18) and Cowarker who used the second dose thiopentone at a dose of 2.5 mg/kg over 30 seconds before laryngoscopy.…”
Section: Discussionsupporting
confidence: 91%
“…Addition of induction agents 12 or inhalational anesthetics 13 are frequently used before tracheal intubation to blunt circulatory responses, but may deepen both the hypnotic and antinociceptive components of anesthesia. We found that normotensive and hypertensive patients showed similar increases in BIS after tracheal intubation, indicating that there was no difference in the intubation-induced arousal responses in these two groups of patients.…”
Section: Méthode : Trois Minutes Après L'induction De L'anesthésie Avmentioning
confidence: 99%